PRINCIPLES OF PREGRAVID PREPARATION AND MANAGEMENT OF PREGNANT WOMEN WITH PREECLAMPSIA IN THE BACKGROUND OF THROMBOPHILIA - H. L. Atabaeva (IRBIS LLC, 2017)
Objective. To study the pathogenetic significance of genetic and acquired thrombophilia and improve the principles of prevention of preeclampsia.Materials and Methods. 65 patients were examined, who were divided into 2 groups: I group consisted of 35 women - pregnant women with repeated episodes of preeclampsia in the present pregnancy, in the II group consisted of 30 primigravida women with preeclampsia during the current pregnancy.Results. Pathogenetically substantiated prophylaxis with low molecular weight heparin, vitamins and antioxidants in patients with preeclampsia and multigenic thrombophilia in early pregnancy has improved during gestation and perinatal outcomes in pregnant women. This was significantly better outcomes have occurred in patients who were treated with early pregnancy and childbearing cycle.Conclusion. Early (antenatal) diagnosis, prevention and differentiated pathogenetic therapy can not only prevent the development of obstetric complications, and, consequently, reduce maternal mortality and morbidity, and improve perinatal outcomes in patients with various forms of thrombophilia. Pathogenic prevention of recurrent episodes of preeclampsia should be based on prevention of manifestations of pro-inflammatory status and genetic thrombophilia.